Carbonation and permeability characteristics of modern South African concretes - Omar, Nabeel (Department of Civil Engineering, 2019)
The world’s exponential growth in urbanisation has placed significant pressure on the construction industry to support development by expanding its provision of infrastructure. There is expected to be a rapid increase in the consumption of structural concrete to meet the associated requirements. This increase in concrete consumption has adverse effects on the environment. Firstly, the production of cement, one of the main components of concrete, is regarded as a system of energy-intensive processes. Secondly, the production of Portland cement (PC) releases a substantial amount of greenhouse gases (such as carbon dioxide), which in turn contributes to the global warming phenomenon. In addition to the change in demand for concrete over time, its composition and mix proportions have indeed also undergone a significant evolution. Concrete is becoming more sophisticated and complex. The construction industry has introduced mineral admixtures as partial replacement of PC in the attempt to mitigate the negative environmental impact of cement production. The use of mineral admixtures has positive economic and environmental benefits. In the context of concrete durability, the use of mineral admixtures has the potential to improve the performance of concrete by mitigating the deterioration processes occurring in concrete structures, such as reinforcement corrosion. Reinforcement corrosion is one of the most pervasive concerns within the construction industry. Carbonation is considered as of the main causes contributing to the corrosion phenomenon. The carbonation mechanism entails the reaction between atmospheric carbon dioxide and the cement paste and leads to an altered chemistry within concrete, which eventually causes the depassivation of steel reinforcement. The deterioration of the concrete caused by carbonation can be predicted using the oxygen permeability index (OPI) test results as an input parameter in the appropriate carbonation prediction model. While South Africa has developed carbonation durability prediction models that can predict the performance of conventional concrete mixes (concrete containing 30% fly ash, 50% slag, 10% silica fume) relatively well, this formulation of the carbonation model was instituted approximately twenty years ago and is considered outdated. Therefore, this research seeks to investigate whether the previously established correlation between carbonation and oxygen permeability is still relevant for modern South African concretes. In this study, concrete constituting of different mineral admixtures at varying PC replacement levels or the use of chemical admixtures is defined as modern concrete. The experimental work included investigating the permeability and carbonation performance of modern concretes made with modern binder types at varying binder replacement levels and binder combinations, including binary and ternary cement blends at two water:binder ratios of 0,50 and 0,65. This included addition of fly ash (FA) (20%-50% in 10% increments), blast furnace slag (BS) (20%- 60% in 10% increments), Corex slag (CS) (20%-60% in 20% increments), and limestone (10% and 20%). For ternary blends, the concrete was limited to three mixes, that is, 5% SF with either 25% FA, 25% BS or 25% CS. Furthermore, two commercial blended cement products were tested namely CEM II A-L, and CEM Il B-M (L-S) 42,5N, referred to as A-L and B-M. A-L and B-M cement nominally contain 8% L, and 8% L coupled with 25% CS respectively. The OPI test was conducted after 28-days of wet curing. The accelerated carbonation tests were conducted using a phenolphathein indicator solution at 6, 9 and 12 weeks of exposure. Prior the testing, the samples were wet cured for seven days and underwent a preconditioning regime in attempt to minimise the influence of the internal moisture of the concrete affecting the carbonation depth results. A statistical analysis was done on both OPI and the accelerated carbonation results to determine the significance in results with the increase in binder replacement percentage, different binders of the same binder replacement percentage and significance of using ternary mixes in comparison to binary mixes. In conclusion it was found that, generally, mineral admixtures had a statistical insignificant influence on the permeability. This can be attributed to the fact that the control mixes already possessed a high permeability performance i.e. concretes exhibiting relatively low permeabilities. Therefore, the inclusion of a mineral admixture would result in a minor influence on the performance. Regarding carbonation depths, the inclusion of mineral admixtures resulted in a decrease in carbonation performance, as expected. This is attributed to the dilution effect and the pozzolanic effect to some degree, which decreased the amount of carbonatable material that is calcium hydroxide, subsequently decreasing the concrete’s resistance to carbonation. Finally, reasonable correlations were identified between carbonation depth and permeability when all concrete mixes were considered. The direction of the trend showed a positive and negative association when the carbonation coefficient was plotted against k-permeability and OPI respectively. Further investigation of the correlation between carbonation depth and a singular binder type regardless of the replacement level showed an increased in correlation strength between permeability and carbonation. It was concluded that using this approach may provide reasonable correlations for carbonation prediction modelling. However, more testing would be required to confirm the previous statement.